2018
DOI: 10.1007/978-3-030-03189-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Resilience: From Practice to Theory and Back Again

Abstract: This book offers a purposefully broad exploration of resilience: it presents a variety of diverse perspectives in a range of practical contexts across various scales of system from a range of disciplinary positions. One of the core organising principles of this book is a concern with understanding how ideas of resilience can be translated into practice, and how practices of resilience can in turn be theorised and explainedirrespective of whether those practices are conducted at the 'street-level' by frontline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Involving next of kin contributed not only to informing the investigation but also to transparency and trust building at the individual level and potentially to the restoration of resilience at a systemic level because next of kin changed the way regulators investigated and generated new information that could be used for system improvement. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Involving next of kin contributed not only to informing the investigation but also to transparency and trust building at the individual level and potentially to the restoration of resilience at a systemic level because next of kin changed the way regulators investigated and generated new information that could be used for system improvement. 29 …”
Section: Discussionmentioning
confidence: 99%
“…All narratives were developed in researcher pairs according to a predefined template agreed upon in the research team. The narrative development covered the following dimensions based on Macrae and Wiig [ 34 ]: Defining the phenomena of resilience (ca 150–200 words on each question): Resilience for what? (What goals and objectives are resilience supporting?)…”
Section: Methodsmentioning
confidence: 99%
“…2 There is a particular lack of empirical investigations of macro-level activities (ie, actions of governments and regulatory agencies) and their relation to the resilience of healthcare systems. 11,[21][22][23] While the resilience literature on public health responses to natural disasters and outbreaks of infectious disease addresses macro-level concerns, a recent review found that these studies often focus on service delivery, leaving issues such as governance underexplored. 6 As a result, a need exists for investigations of the relationship between government actions and the capacity for resilient performance in healthcare.…”
Section: Introductionmentioning
confidence: 99%